Smart-valleys: A farmer-led approah to fight climate change in Africa - Africa Rice Center (Africa Rice Center, 2020)
Smart-valleys’ is a climate-smart, low-cost, participatory approach to develop lowlands for rice-based systems. The approach is being used by farmers in Benin, Togo, Burkina Faso, Liberia and Sierra Leone and now Cote d’Ivoire. It allows rice yields to double through improved water control, with only limited additional cost for the producers compared to common approaches with high investment costs. Smart-valleys are more sustainable because they are developed and constructed by farmers themselves.